Replicator dynamics in value chains: Explaining some puzzles of market selection - Uwe Cantner; Ivan Savin; Simone Vannuccini (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2016)
The pure model of replicator dynamics though providing important insights in the evolution of markets has not found much of empirical support. This paper extends the model to the case of firms vertically integrated in value chains. We show that i) by taking value chains into account, the replicator dynamics may revert its effect. In these regressive developments of market selection, firms with low fitness expand because of being integrated with highly fit partners, and the other way around; ii) allowing partner's switching within a value chain illustrates that periods of instability in the early stage of industry life-cycle may be the result of an 'optimization' of partners within a value chain providing a novel and simple explanation to the evidence discussed by Mazzucato (1998); iii) there are distinct differences in the contribution to market selection between the layers of a value chain, causing strategic advantages to firms in partnering.
urn:nbn:de:swb:90-523726
Keywords: C63; D24; L14; O32; 330; innovation; replicator dynamics; returns to scale; value chain